AB0302 Can We Use a Validated Synovitis Score Developed for the Follow-Up of RA Patients (the Sonar Score) as a Tool to Predict an Evolution Towards RA in Patients with Polyarthralgia?. (9th June 2015) - Rebell, C.; Ziswiler, H.R.; Dumusc, A.; Lucini, M.; Haintz, J.; So, A.; Zufferey, P.
Abstract : Background: In established RA, musculoskeletal ultrasound (US) is more sensitive than clinical assessment for the detection of synovitis. Few scores US have nevertheless been validated essentially for the follow-up of RA. The SONAR is one of them. It has the particularity to be used in real life practice by many rheumatologists at a national level in Switzerland since 2009. Objectives: The aims of the study was assess the value of the US SONAR as a screening tool to detect early joint involvement in patient complaining of polyarthralgia and to predict the future development of a inflammatory disease in particular RA. Methods: This is a retrospective real life study of 101 consecutive patients seen in investigation in our ambulatory unit between 2009 and 2013 with poly-arthralgia lasting for more than 6 weeks. None met the ACR/EULAR 2010 criteria for RA or for another inflammatory rheumatology disease. A SONAR score was performed for each patient in addition to regular biological and immunological investigations. Based on earlier studies (1, 2), the score was considered as positive, highly suggestive of an inflammatory arthritis, when the total score exceeded 8/66 points or when there were more than two grade two synovitis in B-mode or when any Doppler activity was detected. Five different rheumatologists performed the ultrasound examinations. The follow-up data were extracted from the flow charts of the service or information taken from regular doctors. Results: Complete follow up data could be obtained in 97/101 patients: 75 females. At baseline, 27 patients (28/%) had a positive SONAR score. The base line demographic and biological, immunological characteristics of the SONAR + and SONAR - were similar. The mean (SD) follow-up time was 19 (7) months in both groups. 17 patients developed a clear inflammatory arthritis (11 RA). 55 patients complained of unchanged polyarthralgia, 16 had no remaining symptoms and 9 had a clear degenerative disorder. The Table summarizes the evolution toward RA and non RA inflammatory arthritis in the two groups. Conclusions: Our study suggests that the SONAR score is a useful tool in patients presenting inflammatory polyarthralgia. In presence of ultrasound synovitis, the evolution toward RA or another inflammatory arthritis is significantly more frequent than in absence of such synovitis References: Joint Bone Spine. 2014 Oct;81(5):426-32. Joint Bone Spine. 2014 May;81(3):222-7. Disclosure of Interest: None declared